Analysis of Matters Affecting Employee Job Satisfaction at PT Mitra Andal Sejati - Abdullah, Muhammad (Faculty of Economics and Business, Jenderal Soedirman University, 2023)
This research was conducted to find out specifically about the influence of motivation, compensation, and work environment on employee job satisfaction either partially or simultaneously at PT Mitra Andal Sejati. The type of sampling from this study used probability sampling with a simple random sampling technique which produced 95 respondents. In this research, the authors used the proof of data quality test and classic assumption test, after which it continued with the coefficient of determination test and hypothesis testing (t-test and F-test) using SPSS 25 software. The results showed that 1) there is a partial and significant effect of motivational variables on job satisfaction, 2) there is a partial and significant effect of the compensation variable on job satisfaction, 3) there is a partial and significant effect of the work environment variable on job satisfaction, 4) there is a simultaneous and significant effect of the motivational, compensation variable and work environment on employee job satisfaction.